Screening Methods for Isolation of Biocontrol Epiphytic Yeasts against Penicillium digitatum in Lemons - Pereyra, Martina María; Díaz, Mariana Andrea; Soliz-Santander, Fabricio Fabián; Poehlein, Anja; Meinhardt, Friedhelm; Daniel, Rolf; Dib, Julián Rafael (Journal of fungi (Basel), 2021)
Worldwide, the green rot caused by Penicillium digitatum is one of the most aggressive postharvest diseases of lemons. Searching for sustainable alternatives to chemical fungicides, epiphytic yeasts as potential biocontrol agents were isolated from citrus fruits using a tailor-made selective medium. For disclosing their antagonistic potential against P. digitatum, obtained isolates were subjected to direct screening methods, both in vitro and in vivo. In the course of the primary in vitro screening that comprised dual culture assays, 43 yeast strains displaying antagonistic activities against the pathogen were selected. Subsequently, such strains were subjected to an in vivo screening that consisted of a microscale test, allowing the selection of six yeast strains for further analysis. In the final screening using macroscale in vivo tests, three strains (AcL2, AgL21, and AgL2) displaying the highest efficiencies to control P. digitatum were identified. The protection efficiencies in lemons were 80 (AcL2), 76.7 (AgL21), and 75% (AgL2). Based on sequence analysis of the PCR amplified D1/D2 domains of the 26S rRNA genes, they were identified as representatives of the species Clavispora lusitaniae. Interestingly, the strains exhibited a broad action spectrum among citrus fruits as they were also able to combat the green mold disease in grapefruit and two orange varieties. The direct screening methods applied in this study favored the recovery of efficient candidates for application as biological control agents to combat fungal infestations of citrus fruits.